Sex differences in central and peripheral mechanisms of fatigue in cyclists - Glace, B. W.; Kremenic, I. J.; McHugh, M. P. (European Journal of Applied Physiology, 2013)
We examined peripheral versus central contributions to fatigue in men and women during prolonged cycling using a peripheral nerve magnetic stimulation-based technique. 11 men (41 ± 3 years) and 9 women (38 ± 2 years) cycled for 2 h at ventilatory threshold with 5, 1-min sprints interspersed, followed by a 3-km time trial. Quadriceps strength testing was performed isometrically in a semi-reclined position pre- and post-cycling: (1) MVC; (2) MVC with superimposed 3-s magnetic stimulation to measure central activation ratio (CAR), a measure of central fatigue; (3) peripheral magnetic stimulation (PMS) alone of the femoral nerve in a 4-s pulse train, a measure of peripheral fatigue. Data were analyzed with mixed model ANOVA. When adjusted for body mass, men and women had similar strength (p = 0.876), and changes in MVC with time were similar between sexes, declining 22 % in men and 16 % in women (p = 0.360). CAR was similar between sexes and decreased 15 % (effect of time, p < 0.001). Changes in PMS-elicited force were different between sexes: only men lost stimulated strength (6.30 to 5.21 vs. 5.48 to 5.53 N kg-1, interaction p = 0.036). Results clearly demonstrate that quadriceps fatigue after >2 h of cycling was of both central and peripheral origin in men but solely due to central mechanisms in women.